ANALISIS STILISTIKA PADA SURAH AL-QIYĀMAH - Ana Barikatul Laili; Delta Yaumin Nahri (REVELATIA: Jurnal Ilmu Al-Qur'`an dan Tafsir, 2021)
The stylistic approach provides a new perspective in the literature studies, especially Qur'anic research. Understanding the Qur'an from a stylistic overview can explain the use of certain words or language structures that distinguish between works. It reveals the characteristics, implied meanings, and beauty of the structure of the Qur'anic text as the primary aspect of the miracles of the Qur'an. The euphemism of the composition of the Qur'an can be seen, for example, in surah al-Qiyāmah. Surah al-Qiyāmah, classified as a makkiyah surah, contains matters relating to the final day, starting from the sacratulmaut stage to the description of the Day of Judgment. Descriptive research with Stylistic analysis in this article, reveals the findings of four aspects of the Stylistics of the Qur'an contained in surah al-Qiyāmah; phonology, morphology, syntax, and imagery. On the phonological aspect, including; fricative, plosive, mukarrarah, and semi-vocal consonants. From the morphological aspect, there are forms of verbs (al-māḍi, al-muḍāri‘ and af‘al al-majhul) which have various meanings. Aspects of syntax contribute to the style of language such as; al-taqdm wa al-ta'khīr, repetition, imperative sentences, and interrogative sentences. Meanwhile, in the imagery aspect, alliteration, assonance, polysindenton, erotic, tautology, ellipsis, synecdoche, and hypalase styles are found.